APPLICATION OF BENZYL ADENINE AND IAA ON THE GROWTH OF BANANA BARANGAN SUBCULTURE (Musa acuminata L.) - Setyawati, Andriyana; Samanhudi, Samanhudi; Purwanto, Edi; Arniputri, Retna Bandriyati; Setyawan, Kevin Putra; Cahyadi, Muhammad Aji (Journal of Biodiversity and Biotechnology, 2024)
Barangan banana is a banana variety that has high economic value, but its production is still carried out conventionally, resulting in limited barangan bananas on the market. The use of tissue culture methods can quickly produce high-quality, disease-free plants regardless of seasonal conditions. The aim of this research is to determine the effect of providing the best ZPT IAA and BA for the growth of the Barangan banana planet. The research was conducted in August-October 2023 at the Biotechnology and Plant Physiology Laboratory, Sebelas Maret University. This research used a two-factor Completely Randomized Design (CRD) with 6 replications. The first factor was the use of ZPT Indole Acetic Acid (concentrations 0, 0.5, 1, and 1.5 ppm and the second factor was the use of ZPT Benzyl Adenine (0, 0.5, 1, 1.5 ppm). The variables observed were root emergence time, number of roots, root length, time of leaf emergence, number of leaves, time of shoot emergence, number of shoots, and height of shoots. The observed data were analyzed using Analysis of Variance (ANOVA) with a 5% level test and if there was a significant difference, it was continued with Duncan's Multiple Range Test (DMRT) at the level 5%. The results showed that giving 0.5 ppm IAA increased root length; 0.5 ppm IAA was given optimally for root formation; and 1 ppm IAA increased the shoot height of the Barangan banana plnalet. Giving BA 0.5 ppm root number; BA 1, 5 ppm produces the highest number of leaves; BA 1 ppm increases shoot height of barangan banana plantlets.